Highly Proton Conductive sPPEK /SSi-GO Composite Membranes for Proton Exchange Membranes Fuel Cells. (21st April 2017) - Zhu, Xiuling; Huang, Jianyu; Jin, Cuihong; Zhang, Shuai; Li, Shuai; Jiang, Ben; Sun, Fang
Abstract : Sulfonated organosilane graphene oxides (SSi-GO) were synthesized by grafting 3-mercaptopropyl trimethoxysilane (MTPS) with graphene oxide (GO) and follow-up oxidation of hydrogen peroxide. Then, the SSi-GO was introduced into sulfonated poly(phthalazinone ether ketone) (sPPEK) to obtain composite membranes, and the physicochemical and electrochemical properties were examined systematically. The results show that the proton conductivity of 10% SSi-GO composite membranes was improved greatly from 0.094 S/cm to 0.22 S/cm from 30-80℃, comparing to the 0.089-0.17 S/cm from 30-80℃ of Nafion 117, which indicates that the sPPEK/SSi-GO composite membranes have potential prospect for proton exchange membranes fuel cells.